5 ASSOCIATION OF UGT1A1 POLYMORPHISM AND BILIRUBIN LEVELS IN FEMALE MULTI-RACIAL/ETHNIC COHORT. (1st March 2005) - Hong, A. L.; Kim, H. J.; Niu, Q.; Cummings, S. A.; Huo, D.; Olopade, O. I.
Abstract : Background: UGT1A1 is key in bilirubin catabolism as well as estradiol, xenobiotic, and drug metabolism. Low expression of UGT1A1 due to increased TA repeats has been associated with bilirubin levels, increased drug toxicity, and cancer risk in select populations (Bosma et al., 1995; Iyer et. al. 1997; Ando et al., 2000; Adegoke et al, 2004; Duguay et al, 2004). We have recently identified novel functional variants (SNPs) within the evolutionarily conserved regions of UGT1A1, including ethnic specific SNPs. To test the hypothesis that mean serum bilirubin level (MSBL) is higher in cancer cases compared to controls, varies by gender, race, and ethnicity, and is correlated to UGT1AI genotypes, we performed a preliminary analysis of bilirubin levels in an ethnically diverse cohort of women seen in a cancer risk clinic under IRB approved protocols. Methods: UGT1A1 SNPs, including ethnic specific SNPs, and TA repeat number will be typed in each individual and genotypes as well as specific haplotypes will be correlated to bilirubin levels. Results: Of 787 patients evaluated in the clinic, 158 individuals had DNA samples and bilirubin levels available. Of these, 124 were female. There were 36 African Americans (AA) and 88 Caucasians (CA); 97 were affected with cancer and 27 were unaffected members of high-risk families. Total sample had a MSBL of 0.45 ml/dL ± 0.19. Consistent with previous reports, we observed significant variability in bilirubin levels across racial/ethnic groups. AA had a MSBL of 0.39 ± 0.17 while CA had a MSBL of 0.47 ± 0.19 with a p-value of 0.004 from a t-test after log transformation. Conclusions: We have established in our population that MSBL is lower in AA compared to CA, differences that could potentially explain disparities in health outcomes among AA and CA populations. Future work will correlate bilirubin levels to UGT1A1 genotypes to determine if serum bilirubin levels can be used as surrogate for specific genotypes that correlate with cancer risk in a larger study of cancer cases and controls.